Analisis Penerapan Prinsip 5S pada Gudang Non-Medis di Rumah Sakit Daerah UOBK - Anbiya, Henry Hafidz; Haikal, A. Anas (Fakultas Teknik Universitas Tulang Bawang, 2025)
UOBK Regional General Hospital (RSUD) is a service industry that considers optimal service quality for patients. One way to optimize services is by optimizing non-medical service equipment and storage warehouses. Analysis of the implementation of the 5S Principles and recommendations for improvements were carried out at the Non-Medical Warehouse at UOBK Regional Hospital to support increasing worker productivity which is expected to have an impact on the quality of hospital services. As a result of the research we conducted, the application of the 5S Principles at UOBK Hospital needs to be improved. This is proven in the analysis of the implementation of the 5S Principles that has been carried out, many facts were found that did not apply the 5S Principles. So it is necessary to increase knowledge about the 5S Principles and joint commitment between elements in the Non-Medical Warehouse at UOBK Regional Hospital Keywords: 5S Principles, Hospital, Non-Medical, Warehouse